PENGARUH KONSEP DIRI DAN PERILAKU BELAJAR TERHADAP PRESTASI BELAJAR PAI DI SMAN 04 KECAMATAN KEDURANG KABUPATEN BENGKULU SELATAN - Anisatul Hasanah (UIN Fatmawati Sukarno Bengkulu, 2020)
The purpose of research to determine whether the concept of self positively affect the learning achievement of Islamic Religious Education students. Second Is the behavior of learning positively affect the learning achievement of Islamic Religious Education students, Third Is self concept and learning behavior have an effect on to learning achievement of Islamic Religion High School student of State 04 Kedurang District of South Bengkulu Regency. The method used in this study is descriptive quantitative because this research is presented with numbers. The results showed that self-concept directly positive effect on learning achievement Islamic Religious Education In School Mengah Atas Negeri Kedurang Subdistrict of 0,379 (37,9)%, Both Behavior of learning gives a positive influence on learning achievement of .0,670 (67,0)% Third there is influence of self concept and behavior Learning together to positively influence the learning achievement of Islamic Religious Education In School Mengah Atas Negeri 04 Kedurang District of South Bengkulu 0,815 (81,5) %